5m-37=4m+7(m-1)

Simple and best practice solution for 5m-37=4m+7(m-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m-37=4m+7(m-1) equation:



5m-37=4m+7(m-1)
We move all terms to the left:
5m-37-(4m+7(m-1))=0
We calculate terms in parentheses: -(4m+7(m-1)), so:
4m+7(m-1)
We multiply parentheses
4m+7m-7
We add all the numbers together, and all the variables
11m-7
Back to the equation:
-(11m-7)
We get rid of parentheses
5m-11m+7-37=0
We add all the numbers together, and all the variables
-6m-30=0
We move all terms containing m to the left, all other terms to the right
-6m=30
m=30/-6
m=-5

See similar equations:

| 5x+5/6=10 | | 5m-37=4m+7(m-1 | | x/3=x+6/7.5 | | 7x-1.5=-4x+11.4 | | 27=a/0.8​ | | 2y-24=-10y | | (-8)=46-x | | 11y-12=-1+10y | | 2.2n=418 | | 2–3n=8 | | √32x+121−7=−2 | | 9=3+t/4 | | `4y+3=31` | | -x+17=3x+7 | | 9=3+t4 | | -2x(6x-7)=0 | | 1.2/c=0.3 | | -7=15c-6c+5 | | -2(5x+9)=2(-4) | | 6=5(x-6)-2x | | 3x+9+x-11=180 | | -125+4x=-13x+215 | | −3=m+4 | | 5y-8=7y+22 | | 3x–104=x+74 | | y+(−4)=7 | | -84+12x=4x+156 | | G(x)=5(x+11) | | 22.1-x=-16.4 | | -5x-23=-8x+22 | | -2x-70=-12x+100 | | -5x-2.8=-8x+0.4 |

Equations solver categories